Endoscopic Follow-Up of Positive Fecal Occult Blood Testing in the Ontario FOBT Project - Lawrence Paszat; Linda Rabeneck; Lori Kiefer; Verna Mai; Paul Ritvo; Terry Sullivan (Canadian Journal of Gastroenterology)
BACKGROUND: The Ontario FOBT Project is a pilot study of fecal occult blood testing (FOBT) for colorectal cancer screening conducted among age-eligible volunteers (50 to 75 years) in 12 of 37 public health regions in Ontario.